IMPLEMENTASI PERATURAN MENTERI KESEHATAN NO 20 TAHUN 2019 TENTANG PENYELENGGARAAN PELAYANAN TELEMEDICINE ANTAR FASILITAS PELAYANAN KESEHATAN (STUDI DI RS HERMINA PADANG) - Mona, Deli; Uning, Uning; Adnan, Surma; Musta, Arif Paria (Universitas Fort De Kock, 2024)
The Covid-19 pandemic has made regulations regarding physical distancing. Alternative efforts are needed to provide health facilities by providing services to the community without having to go to the hospital, otherwise known as telemedicine. Therefore, the formulation of the problem is: 1) How is the implementation of the Regulation of the Minister of Health of the Republic of Indonesia Number 20 of 2019 concerning the Implementation of Telemedicine Services at Hermina Hospital, 2) What are the obstacles in implementing the Regulation of the Minister of Health of the Republic of Indonesia Number 20 of 2019 concerning the Implementation of Telemedicine Services in Hospitals Hermina, 3) What are the efforts in implementing the Regulation of the Minister of Health of the Republic of Indonesia Number 20 of 2019 concerning the Implementation of Telemedicine Services. The research used sociological juridical method. The data used are primary data, obtained from interviews. Secondary data obtained from document study. The data collected was processed and analyzed by qualitative analysis methods. The result is that the Minister of Health Regulation Number 20 of 2019 has not been implemented properly. The obstacle is that not all doctors/specialists who provide telemedicine services and applications are not yet optimal. The effort is making a decree for doctors and working together to get an official telemedicine application.